A Dealer Centric Analysis of Competitive Marketing Strategies of Cement Companies in India - Gautam, Amit (Indian Journal of Marketing, 2008)
In today's dynamic business world, marketing in case of cement industry has a very vital role to play. Since all big names are involved in cement manufacturing and with new technological know how available at the disposal for all of them, the quality of cement manufactured by every big company is almost same, the only thing which makes the difference is the marketing. The company which has most sophisticated network of marketing will win the battle i.e., will be the market leader. Therefore due to this fact the main thrust of cement companies always goes behind marketing. This paper tries to visualize the current state of cement dealers, analyzing their role in complementing the marketing campaigns of different companies and the essential characteristics that govern them.